ANALISIS TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI KARET DI DESA LUBUK BATANG LAMA KECAMATAN LUBUK BATANG KABUPATEN OKU (JASEP, 2017)
This study analyzes the level of Farmer Households Food Security in the village of Lubuk Batang Rubber Old District of Lubuk Batang Ulu Ogan Ogan. Location data collection study was conducted in November to December 2016. The research method used is survey method with the help of a questionnaire as a tool for research that takes a sample of a population. The data used are primary and secondary data. The data was processed using descriptive analysis of qualitative and analyzed using measures based on the share of household food expenditure rubber farmers (Purwaningsih 2010). Based on the results, the level of household food security rubber farmers in the village of Lubuk Batang Batang Lubuk Old District of Ulu Ogan Ogan at the level of food security for the expenditure share of 42.53% or <60% of total household expenditure.